STRATEGI KETAHANAN PANGAN MELALUI UPAYA PENINGKATAN EKONOMI KELURAHAN SUDAJAYA HILIR - Yanti Andriani, Neneng; Aziz, Abdul; Jabar, Abdul; Rismawati, Dea; Hendrik, Hendrik; Ajizah, Nur; Anggraeni, Putri; Haulah, Suci (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2023)
Student Work Class (KKM) is a form of community service carried out by students in an interdisciplinary, institutional, and partnership manner as one of the manifestations of STIE PASIM SUKABUMI. The community service program is seen as a program that must be implemented, both by lecturers and by students, based on the principles of academic, entrepreneurial, and professional competence, so as to produce quality, relevant, and synergistic community service programs in increase community empowerment. This study aims to analyze the priority role of community service and the influence of internalization of innovation, and changes in the external environment and food security strategies with efforts to improve the economy of the downstream Sudajaya sub-district. Developing micro, small and medium enterprises (MSMEs), especially MSMEs in the downstream Sudajaya sub-district. Namely UMKM Bread NS Sampora, Memories donuts, Crafts from bamboo and magot cultivation farms. The problems faced by all MSMEs in the Sudjaya Hilir sub-district are related to packaging and digital marketing.